The influence of leadership, workload, and work environment on healthcare workers’ job satisfaction from an educational and curricular perspective - Nurhaniza, Irma; Dyahrini, Wien (ARKA INSTITUTE, 2025)
This study aims to analyze the influence of leadership, workload, and work environment on job satisfaction among healthcare workers at the Cibiru District Community Health Center in Bandung and examine their relevance to education and competency development. The research method used was quantitative descriptive research with a population of all employees at the Cibiru District Community Health Center in Bandung, totaling 74 respondents. Data were collected through questionnaires and interviews. The results of multiple linear regression analysis indicate that leadership has a positive and significant influence on employee work performance. The work environment also has a positive and significant influence on employee performance. However, workload does not show a significant influence on job satisfaction, although the direction of the relationship is negative. Simultaneously, the variables Leadership, Workload, and Work Environment significantly influence employee job satisfaction, with 44% of the variation in work levels explained by this model. These findings confirm that formal education, leadership training, and a healthcare curriculum that integrates managerial and leadership aspects are important foundations in improving healthcare worker satisfaction and performance. This study implies the need to strengthen the educational dimensions and healthcare curriculum to develop effective leaders, create a supportive work environment, and encourage improved service quality in healthcare centers.